Solution-processed pristine metal oxides as electron-transporting materials for perovskite solar cells - Sharma, Harshit; Srivastava, Ritu (Frontiers in Electronic Materials, 2023)
In recent years, perovskite material based photovoltaic devices have got a great attention of the researchers because of an expeditious improvement in their efficiency from 3.8% to over 25%. The electron transport layer (ETL) which functions for extraction and transportation of photogenerated electrons from active perovskite material to the electrodes is a vital part of these perovskite solar cells (PSCs). The optoelectronic properties of these ETL material also have an impact on the performance of these PSCs and for commercialized flexible PSCs a low temperature and solution processable ETLs having the high stability and suitable optoelectronic properties are needed. In this regard, the solution processable films of different metal oxides have been largely investigated by the many research groups. So, this review summarizes the optoelectronic properties of the different metal oxide based ETLs and the development in performance of the PSCs which have a solution processable metal oxides as ETLs.